Quality Evaluation of Dried Red Chili (Capsicum annuum L) with Convection and Radiation Drying Methods - Ridwan Rachmat; Helmi Harris; Amar Ma'ruf; Aditia Ginantaka (JURNAL AGROINDUSTRI HALAL, 2023)
Red chili is one of the most important horticultural products. Red chili is a perishable commodity that easily damages, caused by bacteria or fungal. Changes in the enzyme activity in chili that cause shrinkage or wrinkles during storage, transport, and fresh chili packing can reduce the market price. The objective of this study was to determine the changes that occur in the drying process. The material used in this study was red chili (Capsicum annuum). The equipment used Far Infrared Ray (FIR) dryer, electrical oven, and equipment for analysis. This study employed a randomized block design consisting of 5 drying treatments with 3 replications for each treatment. This study showed that the use of FIR dryer at 50°C for drying red chilies gave the best drying time (11 hours), compares with sun drying (38 hours), and oven 50°C (46 hours). The rehydration property of the water content produced is also not much different from an oven dryer at 60°C (39 hours) and sun drying. Drying with FIR caused loss of volatile more than the oven method, however drying time for FIR dryer at 50oC and 60oC were shorter. Air quality levels, ash levels, VRS, and the yield obtained was not significantly different from the oven dryer which took longer drying time. Far Infrared dryer (FIR) and sun drying are radiation drying method, and electric oven as a convection method can provide the best results.